2020
DOI: 10.3389/fgene.2020.574145
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 Knockdown Inhibits Retinoblastoma Progression by miR-3619-5p/LASP1 Axis

Abstract: Retinoblastoma (RB) is the most common intraocular tumor in childhood. Long non-coding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 (NTAT1) has been reported to be related to RB progression. This study aims to study the molecular mechanism of NEAT1 in regulating cell cycle, proliferation, apoptosis, migration, and invasion in RB. The expression levels of NEAT1 and miR-3619-5p were detected by quantitative real-time polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…The contribution of NEAT1 to cancer progression has also been studied in other cancers, including cervical cancer [ 77 ], cholangiocarcinoma [ 78 ], endometrial cancer [ 79 ], esophageal carcinoma [ 80 ], gallbladder cancer [ 81 ], glioblastoma [ 82 ], Hodgkin’s lymphoma [ 83 ], laryngeal carcinoma [ 84 ], melanoma [ 85 ], multiple myeloma [ 11 ], nasopharyngeal carcinoma [ 86 ], osteosarcoma [ 87 ], pancreatic carcinoma [ 88 ], retinoblastoma [ 89 ], thyroid cancer [ 90 ], and tongue carcinoma [ 91 ]. In those cancers, NEAT1 plays a pro-proliferative role and promotes the progression of cancer by upregulating the expression of some oncogenes or downregulating the expression of some tumor suppressor genes.…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“…The contribution of NEAT1 to cancer progression has also been studied in other cancers, including cervical cancer [ 77 ], cholangiocarcinoma [ 78 ], endometrial cancer [ 79 ], esophageal carcinoma [ 80 ], gallbladder cancer [ 81 ], glioblastoma [ 82 ], Hodgkin’s lymphoma [ 83 ], laryngeal carcinoma [ 84 ], melanoma [ 85 ], multiple myeloma [ 11 ], nasopharyngeal carcinoma [ 86 ], osteosarcoma [ 87 ], pancreatic carcinoma [ 88 ], retinoblastoma [ 89 ], thyroid cancer [ 90 ], and tongue carcinoma [ 91 ]. In those cancers, NEAT1 plays a pro-proliferative role and promotes the progression of cancer by upregulating the expression of some oncogenes or downregulating the expression of some tumor suppressor genes.…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“…Bioinformatics analyses in the present study were able to confirm the association between the upregulation of LASP1 expression in liver cancer and liver cancer prognosis. Further studies have reported that LASP1 is involved in cellular migration, invasion, proliferation and apoptosis through several mechanisms, such as participation in signaling pathways, m6A methylation modification or influencing the tumor microenvironment (30)(31)(32)(33)(34). In addition, progress has been made in terms of ongoing therapeutic research seeking to target LASP1 (35).…”
Section: Discussionmentioning
confidence: 99%
“…Another study with a novel research concept suggested that miR-302 and GCNT3 can both regulate the ERK pathway and epithelialmesenchymal transition and could potentially be cancer treatment targets (28). Several basic studies have verified that mir-3619, a relatively newly discovered miRNA, can play a regulatory role in the occurrence and development of tumors through the regulatory axis proposed based on the ceRNA hypothesis (29)(30)(31). Nonetheless, the discovery of other modes of action of mir-3619 requires more effort.…”
Section: Discussionmentioning
confidence: 99%